2021
DOI: 10.3390/plants10102170
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Chlorpyrifos Toxicity in Maize (Zea mays L.) by Reducing Its Uptake and Oxidative Stress in Response to Soil-Applied Compost and Biochar Amendments

Abstract: Chlorpyrifos (CP) is a pesticide used extensively in agricultural crops. Residual CP has been found in a variety of soils, vegetables and fruits indicating a serious danger to humans. Therefore, it is necessary to restrict its entry into agricultural products for food safety. A wire-house pot experiment was conducted with maize plants in biochar- and compost-amended soil (at 0.25% and 0.50%, respectively, in weight-by-weight composition) contaminated with 100 and 200 mg kg−1 of CP, respectively. Results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 55 publications
(71 reference statements)
1
6
1
Order By: Relevance
“…These results are indirectly in line with previous studies wherein BC application alleviated oxidative stress in Brassica chinensis, Carthamus tinctorius, Zea mays, Setaria italica, and Eisenia fetida under different abiotic-stress conditions [34,66,[87][88][89]. However, the current study provides new insights into ROS-MG-induced oxidative stress and its alleviation by BC application.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are indirectly in line with previous studies wherein BC application alleviated oxidative stress in Brassica chinensis, Carthamus tinctorius, Zea mays, Setaria italica, and Eisenia fetida under different abiotic-stress conditions [34,66,[87][88][89]. However, the current study provides new insights into ROS-MG-induced oxidative stress and its alleviation by BC application.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have demonstrated that, under water stress, maize and chickpea plants hyper-accumulated tryptophan, phenylalanine, proline, and tyrosine [83,93]. Contrary to these findings, the current study revealed that amino acid substantially reduced under drought stress in L. fusca plants [2,87,[94][95][96][97][98]. Sugars are the most abundant group of organic molecules in plants [2,99].…”
Section: Discussioncontrasting
confidence: 88%
“…Stress conditions can disturb the dynamic equilibrium of reactive oxygen species (ROS) production and elimination under normal growth in plants (Javed et al, 2021), which promotes ROS accumulation and membrane lipid peroxidation, and disrupts the structure and function of the cell membrane system (Aziz et al, 2021;Gill et al, 2021). It was reported that an excess of Cd can increase lipid peroxidation and MDA, an oxidized product of membrane lipids, indicating the prevalence of oxidative stress and membrane damage (Rizwan et al, 2019).…”
Section: )mentioning
confidence: 99%
“…SOD is one of the special mechanisms developed by plants to detoxify superoxide radicals and can be used as an index in detecting varieties with stress resistance, where plant genotypes that are more resistant producehigh SOD values in leaves according to research by Khayatnezhad & Gholamin (2021). In the research of Aziz et al (2021) corn plants that were stressed due to stress showed a significantly increased SOD activity, in which case SOD played an important role in forming H 2 O 2 in free radical dismutation.…”
Section: Treatmentmentioning
confidence: 99%